2010
DOI: 10.5483/bmbrep.2010.43.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA analysis of ancient human bones excavated from Nukdo island, S.Korea

Abstract: We have performed analyses using ancient DNA extracted from 25 excavated human bones, estimating around the 1 st century B.C. Ancient human bones were obtained from Nukdo Island, which is located off of the Korean peninsula of East Asia. We made concerted efforts to extract ancient DNA of high quality and to obtain reproducible PCR products, as this was a primary consideration for this extensive kind of undertaking. We performed PCR amplifications for several regions of the mitochondrial DNA, and could determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…One mtDNA haplogroup found in many Jōmon-associated individuals (e.g. Kanzawa-Kiriyama et al, 2013 ; Adachi et al, 2011 ; Kim et al, 2010 ) as well as Yayoi-associated individuals (Igawa et al, 2009 ) is D4, which is widespread in northern East Asia both in past and present-day populations (e.g. Tanaka et al, 2004 ; Zhao et al, 2010 ; Hong et al, 2014 ; Jeong et al, 2018 ; Lan et al, 2019 ).…”
Section: Jōmon Geneticsmentioning
confidence: 99%
“…One mtDNA haplogroup found in many Jōmon-associated individuals (e.g. Kanzawa-Kiriyama et al, 2013 ; Adachi et al, 2011 ; Kim et al, 2010 ) as well as Yayoi-associated individuals (Igawa et al, 2009 ) is D4, which is widespread in northern East Asia both in past and present-day populations (e.g. Tanaka et al, 2004 ; Zhao et al, 2010 ; Hong et al, 2014 ; Jeong et al, 2018 ; Lan et al, 2019 ).…”
Section: Jōmon Geneticsmentioning
confidence: 99%
“…In the fission yeast Schizosaccharomyces pombe it was shown that Pmp20p (in addition to thioredoxin peroxidase and glutathione peroxidase) inhibited thermal aggregation of citrate synthase at a high temperature (43°C) in vitro . This suggests that at least in S. pombe peroxisomal Pmp20p may have a second function as a molecular chaperone which could be important for organelle quality control (Kim et al, 2010). …”
Section: Peroxisomal Damage and Repair Mechanismsmentioning
confidence: 99%
“…To define haplogroup affiliations, the D-loop HVR1 (positions 15,977–16,399), HVR2 (positions 29–381), and 10 coding regions of mtDNA were amplified by using primer sets presented in S5 Table and sequenced [ 18 , 23 , 66 ]. The primer set used to amplify the coding region containing SNPs for mtDNA haplogroup M was also used to determine the mtDNA haplogroups N and Z; an amplicon produced by the primer set for haplogroup M contained SNP sites for haplogroups N and Z, as well as for M. In addition, the coding region containing SNPs for the mtDNA haplogroups CZ and G was simultaneously amplified by a primer set for CZ.…”
Section: Methodsmentioning
confidence: 99%